Copyright Protection in Israel - Debbie L. Rabina (Information Research: An International Electronic Journal)
The copyright law in effect in Israel today is the 1911 law signed by King George V and absorbed into Israel's legal code with the termination of the British Mandate in 1948. Althoughsome minor amendments and changes were made over the years, a total revision, that would be in accordance with the changes brought on by the digital age, as well as those necessitated as a result of international treaties, is long overdue. Yet, Israel has been slow in amending its copyright legislation, its enforcement of copyright has been inadequate, and the new copyright law has been in the making for years. This article describes and analysis intellectual ownership rights in Israel today, with a particular emphasis on the difficulties of implementing and enforcing a law that did not foresee digital information.